FAKTOR YANG MEMENGARUHI STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS SIDOMULYO KOTA PEKANBARU - Busyra Hanim (LPPM Universitas Abdurrab, 2020)
Toddlerhood is a golden period to optimize growth and brain development, but it becomes a critical period if it does not get the appropriate nutritional intake. Lack of mother’s knowledge about toddlers nutrition, feeding problems, and diet can affect the nutritional status of toddlers. The results of Nutrition Status Monitoring (PSG) in Riau at 2017 based on BB/U index, show that poor nutritional status is 4.3%, malnutrition is 10.4%, and 1.1% over nutrition. Based on data obtained from the Pekanbaru Health Office in 2018 still found cases of malnutrition and Lower Red Line (BGM) in children under five in the working area of Sidomulyo Health Center.The objective of this study was to determine the factors that influence the nutritional status of children under five in the working area of Sidomulyo Health center. The type of research is quantitative with correlation study and cross sectional approach. The study population was all mothers of toddlers totaling 7,341 poeple with 99 poeple sample taken by purposive sampling at Posyandu in the working are of the Sidomulyo Health Center Pekanbaru. The research instrument was questionnaire. Univariate and bivariate data analysis using Chi-Square (X2) correlation test approach. The results showed a significant relationship between maternal knowledge about toddler nutrition p value = 0.000 (p<0.05), OR (Odds Ratio) 9,360 and toddler’s diet p value = 0.001(p<0.05), OR (Odds Ratio) 6,838 with nutritional status of toddlers. The conclusion of this study that there is a significant relationship between mother’s knowledge about toddler nutriton and diet with nutritional status of toddlers. It is recommended that health workers at Sidomulyo Health center conduct a good assessment of toddler’s diet, to give appropriate advice and management to improve the nutritional status of toddlers.